Pengembangan UMKM Melalui Penggunaan Aplikasi Manajemen Keuangan Pada Kelompok Mitra Usaha UMAMI Di Kabupaten Banyuwangi - Handayani, Estu; Sumitro, Arif Hadi; Prasetyo, Nur (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
Economic development in Indonesia cannot be separated from the very important role of UMKM in improving the domestic economy. The biggest contribution of UMKM is that they are able to absorb and provide jobs for many workers. But behind that, UMKM have other challenges such as lack of capital and financial literacy, especially in Banyuwangi Regency. Many UMKM players under the UMAMI association have not been disciplined in preparing financial reports so they have difficulty getting financing from banks. To overcome this, the Abdimas team held mobile application-based financial management training activities to help UMKM players improve their ability to record financial reports in a neat and structured manner.  The training method used in Abdimas activities is a participatory approach which begins with preparation of joint activities with UMAMI partners. The next activity is making a work plan which is followed by implementing activities in the form of training on the use of financial applications and ends with an evaluation to determine the effectiveness of using financial applications. Training in the use of financial applications has a positive impact on UMKM. Where previously training was carried out on financial management applications, 56% of UMKM players thought it was not very important. However, after the training, more than 70% of UMKM players felt satisfied and stated that this application was very useful for UMKM players in making financial reports neater and more structured. Based on the benefits obtained, UMKM players will continue to use financial applications on an ongoing basis to increase the awareness and ability of UMKM players in managing finances using technology.